2009 revised economic competitiveness of 35 Indian states and union territories with relative competitiveness indices of ASEAN China and India economies. - Chia, Kian Yin. (2010)
From the extensive research made on economic competitiveness of world economies prior to our report, it is apparent that the topic has continued to hog the attention of many academic researchers, policy makers and businessmen. In particular, the rapid emergence of India and China in recent years has altered the future outlook of the world economy, allowing them to come under the radar screen of economic competitiveness. Accounting for about 40 percent of the world population, India and China have been frequently labelled as the future superpowers of the world whose economies have vast potential to dictate global wealth. Thus, it is imperative to understand the economic competitiveness of these two huge economies. To allow for a more comprehensive analysis of the economic competitiveness at a microeconomic level, India and China would be studied at a disaggregated level – China by the provinces and India by the states and union territories. The uniqueness of this report is the combined-level of assessment carried out to evaluate their relative economic competitiveness among these 66 economies.